ANALISIS LULUSAN MATEMATIKA FMIPA UNIVERSITAS MATARAM MENGGUNAKAN DIAGRAM KONTROL MULTIVARIATE EXPONENTIALLY WEIGHTED MOVING AVERAGE (MEWMA - Vidya Atika Ramdani; Emmy Dyah Sulistyowati; Lisa Harsyiah (Eigen Mathematics Journal, 2023)
Quality control of Mathematics graduates of FMIPA UNRAM in 2012-2018 with a control chart of the Multivariate Exponentially Weighted Moving Average (MEWMA), is carried out to determine the quality of graduates of the Mathematics Study Program FMIPA UNRAM and to compare the quality of Mathematics graduates FMIPA UNRAM in 2012-2018 using MEWMA and T2 Hotelling control charts. In this test, control was carried out using three control variables, namely the Grade Point Average , length of study , and the number of Semester Credit Units . This study used the weighting value  with the Upper Control Limit (UCL) of 10,685. The results obtained that the control chart formed to show that 42 data are outside the control limits (out of control), which causes the quality of graduates to be out of control. Using the EWMA univariate control chart, it is known that the length of study variable  causes the data to be out of control. Therefore, a revision was made to the MEWMA control chart so that the quality control process for Mathematics FMIPA Mataram University graduates was within the control limits after the second revision. This is indicated by the absence of observation points  outside the control limits so that the quality of mathematics graduates can be said to be good. Furthermore, a comparison of the results of observations with the quality of Mathematics graduates of Mataram University using the T2 Hotelling control chart in the previous study was carried out with the results that there was one data subgroup that was outside the control limit with = 14.5249 which led to the need for one revision of the T2 Hotelling control chart to obtain statistically controlled diagram. Thus, it can be said that the MEWMA control chart is more sensitive than the Hotelling T2 control chart.